Anatomical and radiological study of jugular foramen - Ajay Kumar; Alok Tripathi; Shobhit Raizaday; Shilpi Jain; Satyam Khare; Ram Kumar Kaushik; Hina Kausar; Alok Saxena (Wolters Kluwer Medknow Publications, 2019)
Background and Aim The purpose of present study was to obtain comprehensive data of morphometric and anatomical details of jugular foramen. Materials and Methods The study was performed on 30 dry adult human skulls along with computed tomography (CT) scans from 30 adult patients. The parameters observed were dimensions, shape, margins, confluence, septations, and distance from j'ugular foramen to mastoid base. Result In the dry skull observations, only anteroposterior diameter (APD) was significantly different between the right and left side, while for the CT scan observations both transverse diameter and APD exhibit significant difference. Conclusion We believe that data from the present study will help radiologists and neurosurgeons for diagnosis and treatment of skull base pathology around j'ugular foramen.